Prevalence of Triad-RED-S symptoms in high-level Kenyan male and female distance runners and corresponding control groups. - Onnik, L.; Mooses, M.; Suvi, S.; Haile, D. W.; Ojiambo, R.; Lane, A. R.; Hackney, A. C. (European Journal of Applied Physiology, 2021)
Purpose This study examined and compared select Triad-RED-S components/risk factors in high-level Kenyan male and female distance runners to corresponding control groups; focusing on examining energy intake (EI), bone indices, and hormonal markers.